Convenience Behavior and Being Overweight in Adults: Development and Validation of the Convenience Behavior Questionnaire - Dreher, Matthias; Hoffmann, Sascha W.; Brendel, Conny; Heser, David; Simon, Perikles (Frontiers in Public Health, 2019)
The etiology of overweight and obesity is a mixture of genetic determinants, environmental factors and health behaviors. Especially intra- and interpersonal inactive behaviors, here termed convenience seems to play an important role. The objective was to develop and validate the Convenience Behavior Questionnaire (CBQ) to assess convenience-related items and their association with overweight and obesity in a large population. A sample of 1233 subjects aged 18 to 82 years from six population groups took part in a self-administered questionnaire. Test-retest reliability was estimated and the independent association between convenience-related items and overweight and obesity was investigated. Principal component analysis revealed three factors (avoidance behaviors, social interaction behaviors and domestic environmental factors), which explained 43.5% of the variance contributing to the CBQ. Cronbach's α ranged from 0.80 to 0.89. Test-retest reliability using intra-class correlation was acceptable ≥ 0.70. Forward stepwise logistic regression analysis, including sex, educational level, age and TV viewing on weekends showed a positive relation of convenience behaviors and overweight (OR: 1.40; 95% CI: 1.01-1.96; P=0.048), while physical activity status was not significantly associated with overweight (OR: 1.09; 95% CI: 0.77-1.54; P=0.629). The CBQ seems to be a reliable tool which considers nontraditional behaviors related to overweight development. Interestingly our findings revealed a better relationship between convenience-related behavior with overweight and obesity than the habitual physical activity score.